Growth hormone genotyping by MspI restriction enzyme and PCRRFLP method in Aceh cattle breed at Indrapuri District, Aceh Province, Indonesia - WIDYA PINTAKA BAYU PUTRA; TETY HARTATIK; SUMADI SUMADI (Society for Indonesian Biodiversity, 2014)
Putra WPB, Hartatik T, Sumadi. 2014. Growth hormone genotyping by MspI restriction enzyme and PCR-RFLP method in Aceh cattle breed at Indrapuri District, Aceh Province, Indonesia. Biodiversitas 15: 1-5. The objective of this research was to identify growth hormone (GH) gene in Aceh cattle at Indrapuri’s Breeding and Forage Centre (IBFC) of Aceh Cattle. Forty one cattle consisting of 21 male and 20 female cattle were used in this study. Polymerase Chain Reaction (PCR) - Restriction Fragment Length Polymorphism (RFLP) and sequencing method was used to detect MspI site on GH gene. Based on the sequencing, it can be concluded that all cattle were monomorphic. The frequency of TT genotype and T allele were 1.00 relatively. The transition of C (cytosine) into T (thymine) on 1549 position caused the lost of restriction site. The insertion of T and G (guanine) on 1542 and 1552 position caused the length of GH gene were 329 bp in Aceh cattle.